PERILAKU BALOK KASTELA BENTANG PENDEK DENGAN VARIASI BUKAAN CIRCULAR, DIAMOND DAN HEXAGONAL MENGGUNAKAN METODE ELEMEN HINGGA - Muhtarom, Ahmad; Idris, Yakni; Welly, Welly (Jurusan Teknik Sipil dan Perencanaan Fakultas Teknik Universitas Sriwijaya, 2018)
Opening modification of castellated beam now has varied including circular, diamond and hexagonal, in the selection of openings required data behavior as the basis of planning according to the desired conditions. The purpose of this study is to know the behavior of short-span castellated beam with variations of circular, diamond and hexagonal openings using finite element method. The geometry of the 1 meter span castellated beam used 225x75x7x5 mm. The method used to create a numerical model castellated beam with circular openings that are analyzed using finite element method then verified with experimental model results with geometry, material and loading the same. After the numerical model result closer to the experimental model, then created 5 variations of the geometry of numerical model openings for each variations. The results showed that the variation in the height and width of the same openings in the three types of openings obtained for the circular opening beams have greater deflection than the others because of the larger holes ratio. For diamond opening beams, the ultimate load is greater than the other because the ratio of the smaller holes ratio and for the hexagonal opening beams has the smallest deflection and stress than the others.